A TRYST WITH MODERNITY: VISION AND MISSION OF JAWAHARLAL NEHRU IN NATION BUILDING - Karinchan, Shobha; C., Shalima M. (International Journal of Research -GRANTHAALAYAH, 2026)
Ever since the attainment of freedom, India is striving hard for the upliftment of the rural masses and there lies the real development of the country. The vision has been aptly conjured by the chief architect of modern India, Pandit Jawaharlal Nehru, who left a lasting impression on the socio-economic and political forces and processes in the country. Today, his ideals and goals are still considered the guiding principles for the formulation of the national policy our country, for which he shall be ever remembered.